Evaluation of the global companies’ language strategies to prosper - Marchenkova, Irina N.; Udovikova, Alla A. (Universidade Estadual Paulista, 2021)
In today’s fast-paced world, international companies encounter an intriguing paradox: Technology permits them to attain new audiences worldwide and makes them improve their communication strategies to adjust to those culturally and linguistically diverse areas favorably. The present paper attempts to present an algorithm for applying analytical tools necessary for assessing and managing the language strategies of global companies. To meet that aim, collection and processing, such general scientific methods of knowledge are taken into account. In the process of conducting analytical procedures, a system of indicators was adapted: liquidity, language abilities, communication skills, business activity, financial soundness, and efficiency. Besides translation, localization performs an essential role in international companies’ progress. Big companies are developing their language strategy exceeding simple translation from one language to another. They are somewhat adjusting their overall business and content policy to meet various cultural and linguistic audiences.